Application of Aporrectodea caliginosa to Mitigate the Waste and the Effects of Vermicompost on the Exomorphological Features of Phaseolus vulgaris - Rouf Ahmad Mir; Sarita Shrivastava; Pragya Singh Pawaiya; Hemant Samadhiya (Advances in Agriculture)
Vermin biotechnology is an eco-friendly technique and economically beneficent process to mitigate organic waste. India’s agro-industrial sector contributes colossal wealth of plant materials in the form of compost. The present study aims to publicize soil healthiness and its plant growth supplying possessions further corroborating the use of organic amendments instead of fertilizers. Plastic replicates investigation is an exercise in eighteen replicates in which fifteen were soil amendment treatments: one triplicate-control, 0% vermicompost, 50%, 25%, 12.5%, 6.25%, and 3.125% vermicompost of soil. Containers contained 2 kg soil each, in which seeds are sown, and the measurement of studied traits (length of shoot, length of internodes, flowers, leaves number and number of branches, and rate of germination) was noticed. The earthworms (Eudrilus eugeniae and Aporrectodea caliginosa) feed on waste like broiler droppings, the dung of sheep and cow, leaves, and decomposed wood and convert it into vermicompost, which required 72 days to extenuate the waste. Each setup was conducted on plastic containers, and there would be control and the test at respective experiments. Vermicompost was prepared; obviously, it contains better farming nutrients analyzed by different scientific methods and is very efficient for plant growth and other features. The main objective of the study was the effect of quality vermicompost produced by A. caliginosa on the exomorphology and rate of germination of Phaseolus vulgaris. Different ratios of vermicompost in respective replicates affect plant growth and external morphology, which is directly linked with nutrients present in treated and untreated soil. The outcomes suggested that vermicompost can be overworked as an efficacious biofertilizer.